Short or long? Analyzing the impact of ski pole length on elite ski mountaineers' performance - Verdel, N.; Bortolan, L.; Holmberg, H.-C.; Pellegrini, B.; Supej, M. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Ski mountaineering (SkiMo) is a rapidly growing winter sport, and the 2026 Winter Olympics will feature ski mountaineering for the first time [1]. Olympics competitions will include men's and women's sprint races, as well as a mixed relay event. Sprint races in ski mountaineering consist of short courses with ascents of less than 80 meters, lasting between 180 and 210 seconds [1]. The first round comprises an individual qualification, with athletes starting every 20 seconds. After qualifying, athletes compete against one another in heats of six. The race start is similar to that of cross-country skiing. Studies have shown that cross-country skiers can benefit from using longer poles [2]; therefore, the aim of this study is to test this approach for ski mountaineering athletes.